Determination by indirect complexometry of the main fatty acid components with Ba (II). I.- Determination of fatty acids - Bosch, F.; García Villanova, R. (Ars Pharmaceutica (Internet), 1968)
A new method is proposed for the determination if the main fatty acids that compose fats, after their neutralization with KOH solution, precipitating with excess of standard solution of Cl2Ba and titration of the excess of Ba (II) in the filtrate with AEDT solution of identical molarity, using o-cresolphthalein complexone as indicator. The errors found are small for lauric, myristic, palmitic, stearic, oleic and linoleic acids for concentration of 0.05M and 0.02 M.